Hospital-acquired Respiratory-Tract Infections in the Teaching Hospitals of Sfax - Maissa Ben Jmaa; Sourour Yaich; Houda Ben Ayed; Maroua Trigui; Mariem Ben Hmida; Habib Feki; Jamel Damak (Dr. Sulaiman Al Habib Medical Journal)
Hospital-acquired Respiratory-Tract Infections (HARTIs) are identified as the most frequent type of hospital-acquired infections. They can engender significant morbidity and mortality rates, generating a heavy economic burden, especially in the limited resources countries. In this perspective, this study aimed to determine the prevalence of HARTIs in the University Hospitals (UHs) of Southern Tunisia and to identify their main associated factors. It was a cross-sectional study conducted in the two UHs of Sfax governorate, Tunisia, from July 10 to 24th, 2017, including all hospitalized patients for at least 48 hours. It was a 1-day pass per department and a 1-week survey per UH. In total, 34 cases of HARTIs were notified among 752 surveyed patients, accounting for an overall prevalence of 4.5%. The prevalence of HARTIs in the Intensive Care Units (ICU) was 20.6%. Multivariate logistic regression analysis showed that developing a HARTI in non-ICU was independently associated with tobacco use [Adjusted Odds Ratio (AOR) = 2.83; 95% Confidence Interval (95% CI) = [1.10.7.27]; p = 0.03], central vascular catheter (AOR = 5.70; 95% CI = [1.29.25.15]; p = 0.022) and McCabe Index ≥1 (AOR = 7.38; 95% CI = [2.73.19.97]; p < 0.001). In ICU, only endotracheal tube was independently associated with HARTIs (AOR = 42.5; 95% CI = [4.97.64.13]; p = 0.001). This study illustrated the extent of HARTIs problem threatening the quality of care in Southern Tunisia. Identifying the risk factors of HARTIs in both ICUs and non-ICUs may help healthcare workers to ascertain the avoidability of these infections.